(untitled) (Revista Electrónica Calidad en la Educación Superior, 2019)
This article presents a systematization of practical experience in the use of e-learning in the subject of Risk Management (04054), belonging to the Finance Chair of the School of Administration Sciences (ECA) of the UNED of Costa Rica, during the third academic period 2018. The challenge was to teach the subject under the 100% online modality that was traditionally offered through the traditional distance modality (tutorials, exams, short assignments and research work). The transition began with a curriculum redesign that supported the online offer, and with the technical-pedagogical advice of the Online Learning Program (PAL) of the UNED. The main results obtained were; Offer focused on communication and collaborative work, creation of three groups with the attention of different teachers, an evaluation of the offer was made from the perspective of the teacher and students. Among the main results after the evaluation of the experience, he highlighted the appropriate choice of content, strategies and the challenge of achieving a balance between activities and available time, among other aspects.